Evaluation of Bi25FeO40 obtained from mining waste as a photocatalyst in norfloxacin degradation - Oliveira, Alessandra Raiany; Silva, Vitória Chris Souza; Silva, Alan Michel Souza; Soares, João Maria; Magalhães, Keurison Figueredo; Castro, Suely Sousa Leal de (XIV Encontro de Catálise do Norte, Nordeste e Centro-Oeste, 2024)
Norfloxacin (NOR) is a widely used antibiotic, frequently detected in water bodies, which raises significant environmental concerns, mainly due to its persistence and resistance to conventional wastewater treatment methods. This scenario highlights the need to develop and implement new approaches, such as Advanced Oxidative Processes (AOPs), which have the ability to effectively degrade these organic pollutants. Among the AOPs, heterogeneous photocatalysis stands out, a process that involves the use of a solid catalyst, which, when irradiated, promotes chemical reactions capable of decomposing contaminants [1]. Recently, research focusing on catalysts obtained from mineral waste has gained interest, with bismuth ferrite (Bi25FeO40) being one of these materials, presenting high photocatalytic activity due to its optical properties [2]. In this work, the efficiency of Bi25FeO40 as a photocatalyst in the degradation of NOR, under UV-visible irradiation, was investigated. Bi25FeO40 was synthesized via solid-state reaction and characterized by energy-dispersive X-ray fluorescence spectroscopy (EFRXF), diffuse reflectance spectroscopy (DRS) and X-ray diffraction (XRD). Photolysis and photocatalysis tests were performed in NOR solution (20 ppm), using a concentration of 500 ppm of Bi25FeO40, neutral pH and analyzed by UV-Vis absorption spectroscopy and ion chromatography. XRD analysis of Bi25FeO40 identified the formation of the silenite phase (COD ID 4030661), with cubic symmetry and space group 123, in addition to the presence of a spurious phase BiClO2Pb, with phase fractions of 95.05% and 4.95%, respectively. The band gap of the material was 3.01 eV. The results of the photolysis and photocatalysis tests indicated NOR degradation rates of 21.8% and 42.2%, respectively. The photolysis and photocatalysis processes followed pseudo-first order kinetics, with rate constants of 1.2 x 10-3 min-1 and 2.5 x 10-3 min-1, respectively. In the photocatalysis test, Ion chromatography studies revealed the formation of short-chain organic acids, such as acetate and formate, confirming the degradation of NOR. Thus, the results obtained demonstrate that Bi25FeO40 presents a promising performance in NOR removal under UV-visible irradiation.